2010
DOI: 10.1063/1.3292584
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced multiferroicity in Mg-doped Ca3Co2−xMnxO6

et al.

Abstract: Polycrystalline Ca3−xMgxCo2−yMnyO6 (y∼1.0) samples are prepared in order to investigate the A-site doping effect of Ca3Co2−yMnyO6 (y∼1.0). Compared with Ca3Co2−yMnyO6 (y∼1.0), the ferroelectric polarization and Curie point of Ca3−xMgxCo2−yMnyO6 (y∼1.0) at the maximal doping x∼0.3 are significantly enhanced. The magnetic order of Ca3−xMgxCo2−yMnyO6 (x∼0.3, y∼1.0) and thus ferroelectric order are more robust than the undoped compound. The slight lattice shrinking as a result of Mg substitution may contribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Under the non‐Markovian RTN, mana for both the negative quantum states of qutrit show expected oscillatory behaviour which is persistent for much longer than the non‐Markovian AD. Interestingly, the action of the phase S‐gate [ 90 ] produces the conjugate of both the negative quantum states of the qutrit.…”
Section: Discrete Wigner Negativity and Mana Variation Under Differen...mentioning
confidence: 99%
“…Under the non‐Markovian RTN, mana for both the negative quantum states of qutrit show expected oscillatory behaviour which is persistent for much longer than the non‐Markovian AD. Interestingly, the action of the phase S‐gate [ 90 ] produces the conjugate of both the negative quantum states of the qutrit.…”
Section: Discrete Wigner Negativity and Mana Variation Under Differen...mentioning
confidence: 99%
“…An effective way to address the Ising nature as well as related properties is element substitution, which was reported for Ca 3 Co 2 O 6 [14][15][16][17][18]. For Ca 3 CoMnO 6 , the effects of doping on the Ising nature as well as multiferroicity were seldom reported [19]. The aim of this study is to understand the origin of Ising magnetism of Ca 3 CoMnO 6 by substitution of non-magnetic ion.…”
Section: Introductionmentioning
confidence: 98%
“…The balance between those interactions is so delicate that even small ionic order defect and disruption of some interactions can bring remarkable response in the multiferroic behavior. 21,22 In particular, recent works confirmed that the spin LRO could be survived only in the Co/Mn compensated Ca 3 Co 1þx Mn 1Àx O 6 with reduced ionic order, while the LRO is abruptly lost in the stoichiometric x ¼ 1 state, meeting the best Co/Mn ionic order, 20 thus leading to a suppression of polarization P. 21 However, in this case, the enhancement remains limited and the ferroelectric transition point T FE remains still low, T FE $ 16 K. Meanwhile, in order to stabilize the spin LRO, some frustrated interactions can be disrupted by introducing local Co/Mn chemical mismatch, e.g., deficiency of Mn or Co ions in Ca 3 CoMnO 6 , thus leading to enhanced ferroelectricity and transition temperature. 23 Apart from the above addressed efforts, an alternative approach intending to modulate the Co/Mn spin order and ionic order is to introduce other magnetic ion by substitution of Mn/Co ions based on the Mn-deficiency system.…”
mentioning
confidence: 99%